2017
DOI: 10.1007/s00439-017-1807-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein sequestration as a normal function of long noncoding RNAs and a pathogenic mechanism of RNAs containing nucleotide repeat expansions

Abstract: An emerging class of long noncoding RNAs (lncRNAs) function as decoy molecules that bind and sequester proteins thereby inhibiting their normal functions. Titration of proteins by lncRNAs has wide-ranging effects affecting nearly all steps in gene expression. While decoy lncRNAs play a role in normal physiology, RNAs expressed from alleles containing nucleotide repeat expansions can be pathogenic due to protein sequestration resulting in disruption of normal functions. This review focuses on commonalities betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 158 publications
0
34
0
Order By: Relevance
“…Just as it seems a combination of mutant and relocalized RBPs can cause aggregation and effect changes in RNA and gene expression, excess repetitive RNAs or those with highly stable structures (Mooers et al 2005;Bernat and Disney 2015;Ciesiolka et al 2017) can sequester RBPs in aggregates, leading to deficiencies in their normal functions ( Fig. 1; Jiang et al 2004;Morriss and Cooper 2017). The convergence of multiple mutations that cause diseases of the neuraxis on mechanisms of RNA and RBP homeostasis suggest that disruption of these pathways represents the most parsimonious candidate for a central mechanism in these diseases (La Spada and Taylor 2010).…”
Section: Mutations Affecting Rbps In Transmentioning
confidence: 99%
“…Just as it seems a combination of mutant and relocalized RBPs can cause aggregation and effect changes in RNA and gene expression, excess repetitive RNAs or those with highly stable structures (Mooers et al 2005;Bernat and Disney 2015;Ciesiolka et al 2017) can sequester RBPs in aggregates, leading to deficiencies in their normal functions ( Fig. 1; Jiang et al 2004;Morriss and Cooper 2017). The convergence of multiple mutations that cause diseases of the neuraxis on mechanisms of RNA and RBP homeostasis suggest that disruption of these pathways represents the most parsimonious candidate for a central mechanism in these diseases (La Spada and Taylor 2010).…”
Section: Mutations Affecting Rbps In Transmentioning
confidence: 99%
“…The concept of competing endogenous RNAs (Tay et al, 2014) is well established, and applies mostly to microRNAs sequestered from target mRNAs. Functional sequestration of RBPs has been instead described for some lncRNAs (Morriss and Cooper, 2017). One of these lncRNA is cyrano, that sponges the HuD paralogue HuR (Kim et al, 2016b), showed previously by us to associate to Y3 (Köhn et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Upon the binding of an miRNA-loaded RISC to SSR tracts, the RISC may remain associated with raceRNAs, which in the case of pathologically expanded SSR tracts, may lead to increased RISC sequestration, affecting global miRNAmediated gene regulation by lowering the availability of Ago proteins for other miRNAs. We also anticipate that structures formed by some SSR-MREs [16] or high-affinity protein binding [13,21] will affect the accessibility of these sequences for raceRNA crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…While such a phenomenon is well described for mRNAs, providing advantageous effects on protein levels [11,12], the functionality of hairpin-forming triplet repeats in ncRNAs must manifest at the DNA/RNA level. Such repeats could contribute to the regulation of the expression of lncRNAs, shape their structure or mediate interactions with other RNAs and RNA-binding proteins (RBPs) [13].…”
Section: Representation Of Triplet Repeat Tracts Varies Between Protementioning
confidence: 99%